The Micronutrient Consumption in Indian Elementary School Children across Socioeconomic Strata - Patki, Kshitija; Sanghi, Divya; Parasher, Raju K.; Bhatnagar, Barkha (International Journal of Child Health and Nutrition, 2021)
Background: The adequate intake of micronutrients in school children has a significant long term beneficial effect on a child’s overall development and performance. Thus, identifying sub-clinical deﬁciencies, monitoring micronutrient intake in a child’s diet, and subsequently treating each is of paramount importance. The present study aimed to determine the daily micronutrient consumption in elementary school children across socioeconomic strata (SCE) compared to age-specific, recommended daily allowance (RDA). Subjects/Methods: Three hundred and sixty-six (366) healthy, school-going girls and boys between the ages of 6 -14 years volunteered for the study. Socioeconomic status was assessed using the urban socioeconomic status grid questionnaire, and micronutrient consumption was determined by the 24-hour recall questionnaire and the Dietcal software. Results: Seventy per cent of the children tested had a BMI in the normal range, and approximately 15.84% of the children were underweight, of which 82% were in the Mid-low SCE strata. Paradoxically, an equal number of children (15%) were overweight, of which 89% belonged to the high SCE strata. Overall, a large number (70-90%) of children were found deficient (compared to RDA) in the intake of micronutrients, and there were significant differences between children belonging to the high and mid-low SCE strata in the intake of Calcium (10 -14 year), Iron (6 - 12 year) and Vitamin B6 (for 10 -14 year). Additionally, the deficiency in the consumption of Calcium, Iron, Vitamin B6, Vitamin 12, and Vitamin A was the most in the older children, while the consumption of Magnesium and Vitamin C across all age groups was within the recommended daily allowance (RDA). Conclusions: Elementary schools across socioeconomic status and age groups reported severe deficiencies in the consumption of micronutrients. Interestingly, in-spite of the accessibility to nutritious food, children belonging to the high SCE strata were also deficient in micronutrient intake. Hence, it is important to re-focus our attention from gross caloric intake to the consumption of micronutrient-rich foods.